Transcriptional regulation by Ferric Uptake Regulator (Fur) in pathogenic bacteria - Hassan, Hosni M.; Troxell, Bryan (Frontiers in Cellular and Infection Microbiology, 2013)
In the ancient anaerobic environment, ferrous iron (Fe2+) was one of the first metal cofactors. Oxygenation of the ancient world challenged bacteria to acquire the insoluble ferric iron (Fe3+) and later to defend against reactive oxygen species (ROS) generated by the Fenton chemistry. To acquire Fe3+, bacteria produce low-molecular weight compounds, known as siderophores, which have extremely high affinity for Fe3+. However, during infection the host restricts iron from pathogens by producing iron- and siderophore-chelating proteins, by exporting iron from intracellular pathogen-containing compartments, and by limiting absorption of dietary iron. Ferric Uptake Regulator (Fur) is a transcription factor which utilizes Fe2+ as a corepressor and represses siderophore synthesis in pathogens. Fur, directly or indirectly, controls expression of enzymes that protect against ROS damage. Thus, the challenges of iron homeostasis and defense against ROS are addressed via Fur. Although the role of Fur as a repressor is well documented, emerging evidence demonstrates that Fur can function as an activator. Fur activation can occur through three distinct mechanisms 1) indirectly via small RNAs, 2) binding at cis regulatory elements that enhance recruitment of the RNA polymerase holoenzyme (RNAP), and 3) functioning as an antirepressor by removing or blocking DNA binding of a repressor of transcription. In addition, Fur homologs control defense against peroxide stress (PerR) and control uptake of other metals such as zinc (Zur) and manganese (Mur) in pathogenic bacteria. Fur family members are important for virulence within bacterial pathogens since mutants of fur, perR, or zur exhibit reduced virulence within numerous animal and plant models of infection. This review focuses on the breadth of Fur regulation in pathogenic bacteria.